The Use of Minipig in Drug Discovery and Development: Pros and Cons of Minipig Selection and Strategies to Use as a Preferred Nonrodent Species. (April 2016) - Heining, Peter; Ruysschaert, Tristan
The pig was introduced more than 20 years ago in drug development following attempts of finding a species that shares better homology with human than the dog, based on biophysiological parameters. However, miniaturization, standardized breeding, and health status control were required before the pig could find a broader than niche application in pharmaceutical industry. During the years of experience with minipigs in pharmaceutical research and the science evolving rapidly, the selection of a nonrodent animal species for preclinical safety testing became primarily driven by pharmacological (target expression homologous function), pharmacokinetic, and biophysiological considerations. This offered a broad field of application for the minipig, besides the well-established use in dermal projects in all areas of drug development but also in novel approaches including genetically modified animals. In this article, we look at recent approaches and requirements in the optimal selection of a nonrodent model in pharmaceutical development and critically ask how good a choice the minipig offers for the scientist, how did the testing environment evolve, and what are the key requirements for a broader use of the minipig compared to the other well-established nonrodent species like dog or monkey.